What is Cyberstalking? A Review of Measurements - Wilson, Chanelle (Journal of interpersonal violence, 2022)
The absence of a widely accepted definition of cyberstalking has resulted in studies operationalizing it in various ways, reducing the comparability and generalizability of findings. The present work examined the most common behaviors and criteria used to operationalize cyberstalking within the quantitative literature. The definitions employed by the studies were evaluated in respect of (a) whether they included a minimum requirement for the number of times the behaviors needed to be repeated in order to be considered ?cyberstalking?; (b) whether victim fear was required for the behaviors to be considered ?cyberstalking?; (c) the timeframe within which the cyberstalking behavior needed to have occurred; and (d) the behaviors identified as indicating cyberstalking. The results demonstrated considerable variation in the specificity of criteria used. Of the 33 studies examined, 45% specifically defined a minimum number of behavioral repetitions required to classify the behaviors as ?cyberstalking,? although there were some discrepancies in the number of behaviors specified across studies. Only 30% of studies included victim fear as a criterion and 70% of studies did not include specific timeframe requirements in which the behaviors needed to have occurred within. The number and description of behaviors included within scales used to measure ?cyberstalking? varied widely. Some instruments utilized as many as 24 different items, whilst others identified cyberstalking through the use of two items. A series of recommendations are advanced aimed at providing criteria for defining and operationalizing cyberstalking that can be employed by future studies, with the ultimate aim of allowing greater comparability between results. From this a consistent knowledge base can be developed, and with it a deeper understanding of cyberstalking and how to counter it.